Does the sex ratio of singleton births after frozen single blastocyst transfer differ in relation to blastocyst development? - Hua Lou; Na Li; Xiaoke Zhang; Ling Sun; Xingling Wang; Dayong Hao; Shihong Cui (BMC, 2020)
Abstract Purpose To investigate the associations between blastocyst development and the sex ratio (male:female) among singleton live births resulting from single-blastocyst frozen embryo transfer (FET) cycles. Methods Patients with singleton live births following the first autologous single FET of non- preimplantation genetic testing (PGT) blastocysts in a single reproductive medicine department between January 2015 and February 2019 were included in this retrospective study. The primary outcome measure was the singleton sex ratio. Multivariable logistic regression models were used to estimate the associations between blastocyst quality and singleton sex ratio after adjustment for some potential confounders. Results There were 638 high-quality and 572 poor-quality single blastocyst FETs, and the blastocysts were conceived via 855 IVF and 355 ICSI treatments. A total of 1210 singleton live births were assessed. High-quality single blastocyst FET resulted in a significantly higher sex ratio than did poor-quality single blastocyst FET (60% vs. 49.7%, P < 0.001). The infertility cause was not associated with sex ratio among singleton live births (P = 0.537). The results of a multivariate analysis revealed that a high-quality blastocyst has a 150% higher probability of being male than a poor-quality blastocyst (adjusted odds ratio (aOR) 1.57; 95% CI 1.24-2, P < 0.001). Among the three blastocyst morphological parameters, Grade B trophectoderm was significantly associated with a higher sex ratio than Grade C (aOR 1.71; 95% CI 1.33-2.21. P < 0.001). Neither expansion degree nor inner cell mass degree were significantly associated with the singleton sex ratio. Conclusions A single high-quality blastocyst FET has a higher chance of resulting in a male infant than a female infant. The results demonstrate that grade B trophectoderm confers benefits in improving the implantation potential of male blastocysts.